Skin cancer awareness campaign in Southern Brazil: A retrospective cohort study - Grasiela Cassia Monteiro; Carolina Matté-Dagostini; Pedro Henrique Lodi; Samantha Lia Ziotti-; Fernando De- (Sociedade Brasileira de Dermatologia (SBD), 2022)
Introduction: Skin cancer is the most frequent malignant neoplasm in Brazil. Its prognosis is directly related to early diagnosis and institution of adequate treatment. The Skin Cancer National Awareness Campaign (SCNAC) is an essential tool to prevent and detect malignant skin lesions. Objectives:: To investigate the incidence of skin cancer and the accuracy of dermoscopy in patients assessed at the SCNAC. Methods: We conducted a retrospective cohort study using directly the data collected from the population assisted at the SCNAC day in 2016, 2017, and 2018 at Clinical Center of the Universidade de Caxias do Sul (CECLIN-UCS). Results: Of the 634 patients included, 105 were referred for biopsy with histopathological study of the lesion. Dermoscopy was suggestive of a malignant lesion in 55 cases. Biopsy diagnosed malignant lesions in 43 patients and benign lesions in 32 patients. Thus, the sensitivity and specificity of the test were 86% and 50%, respectively. The accuracy of dermoscopy in identifying malignant lesions over the three years of the campaign was around 70%. Conclusions: Dermoscopy in SCNAC has a good level of sensitivity and specificity when correlated with final histopathological results.